A Comparative Study between Introvert and Extrovert Students' Personality in Learning English Speaking Skill - Kamalatirrisalah; Cahya Komara (UICELL, 2022)
Speaking is the way of communicating to other people to exchange information. The human personality is seen as one of many factors that might affect speaking ability. Human personalities come in two varieties; introvert and extrovert. In this case, the researchers compared whether students with extroverted personalities would be more proficient in speaking than students with introverted personalities. The researcher used qualitative data with the use of a human personality questionnaire and followed by a speaking test interview with 30 respondents of Al-Chasanah Senior High School students. The findings found that there were 15 students with extroverted personalities and 15 students with introverted personalities. From that division, the researchers exposed only 3 students with extrovert personalities who got a low speaking score or below average compared with students with introvert personalities who got 7 students. It can be concluded that students with extroverted personalities are more proficient in speaking skills than students with introverted personalities.